Electronic Word of Mouth (E-Wom), Celebrity Endorsement and Lifestyle in The Interest of Buying Online Shop Products - Nur Aini Anisa; Andrik Gastri Widjatmoko (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: This research is motivated by the rise of commerce via the internet or so-called electronic commerce (E-commerce). From a businessman's point of view, this is an opportunity for them to increase their business by creating an online shop that is included in several marketplaces. Electronic Word of Mouth (e-wom) includes testimonials from someone who has bought, then there are also figures who are fond of using the product, namely Celebrity endorsers and student lifestyle. The purpose of this study is to reveal how these aspects influence buying interest. Design/methodology/approach: The method in this study uses a quantitative approach by describing multiple linear regressions. The sample research method used is non-probability sampling with the consideration that all populations cannot be used as a sample. The sample obtained was 200 students. Findings: Based on the data analysis, it can be concluded that there is a significant effect of E-WOM on the interest in buying online shop products, there is a significant influence of celebrity endorse on the interest in buying online products, there is a significant influence of lifestyle on the interest in buying online shop products, there is an effect of E-WOM, Celebrity Endorse. and lifestyle simultaneously on the interest in buying online shop products. Research limitations/implications: All respondents of this research are student. Practical implications: Result of this research can be used as references in creating interest in buying online product. Originality/value: This paper is original. Paper type: Research Paper.